Synthesis And Biological Evaluation of Novel Benzopyran-2-One And 1, 2, 4-Triazole Hybrid Derivatives as Cytotoxic Agents - Talwan, Poonam; Gautam, Darsh; Kaushik, Madan; Singh, Ranjit (Journal of Neonatal Surgery, 2025)
Triazole's anti-inflammatory properties in cellular assays and benzopyran-2-one's cytotoxic effects against multi-drug resistant cancer cell lines led us to design and synthesize their hybrid compounds and investigate their antiproliferative activity against a panel of five cancer cell lines. Compounds FE-e, FE-f, FE-o and FE-q displayed significant antiproliferative activities against all the cancer cell lines tested, and IC50 values were in the range of 162-164µM/mL against MDA-MB-231, MCF-7, CaCO2, HUT102 and HUT78 cancer cells, while they were minimally cytotoxic to the HEK-293 and LLC-PK1 normal cell lines. All the compounds were screened for cytotoxicity using MTT assay. Overall, these findings suggest that new benzopyran-2-one-triazole hybrid compounds, particularly FE-e, FE-f, FE-o and FE-q, exhibited promising cytotoxic activity mediated via inhibition of cancer cell proliferation and induction of apoptosis across these cancer cell lines. Additionally, these are selective anticancer agents, potentially safe for human cells, and could be synthesized at low cost.